Synthesis, characterization and hydrogen isotope storage properties of Zr–Ti–Co ternary alloys. (26th January 2017) - Jat, Ram Avtar; Pati, Subhasis; Parida, S.C.; Agarwal, Renu; Mukerjee, S.K.
Abstract: In this study, an attempt has been made to improve the storage properties of ZrCo based alloy, which is being considered as an important material for storage of hydrogen isotopes in the proposed fusion reactors. Herein, we report the hydrogen isotope storage behaviour of titanium doped Zr1−x Tix Co (x = 0, 0.1, 0.2 and 0.3) ternary alloys. Alloys were prepared by arc melting method and characterised by XRD, SEM and EDS. XRD analysis indicates that all ternary alloys form cubic phase similar to ZrCo phase. Hydrogen/deuterium desorption pressure-composition isotherms were generated in the temperature range of 523–583 K, by employing Sieverts' apparatus. All isotherms show a single plateau which confirms the one step absorption–desorption of hydrogen isotopes by Zr1−x Tix Co alloys. Equilibrium plateau pressure of hydrogen/deuterium was found to increase with increase in Ti content of Zr1−x Tix Co alloys. Based on the trend in the equilibrium pressures of the dehydrogenation and de-deuteration reactions, it can be inferred that the partial pressure of tritium over the tritide will be higher than that of deuterium and hydrogen partial pressures. This makes Ti substituted alloys suitable for storage of hydrogen isotopes owing to lower desorption temperature as desired for ITER SDS. Highlights: Hydrogen isotope effect storage behavior of Zr1−x Tix Co alloys was investigated. The equilibrium pressure of D2 is found to be higher than that of H2, at all experimental temperatures. Thermodynamic parameters were calculated for the Zr1−x Tix Co-H2 /D2 systems. Desorption temperature decreases with increase in Ti content.